A evolução da ocupação industrial na região do Grande ABC Paulista - Gomes, Djalma Santana (2008)
This paper tries to evaluate the evolution process of Industrial Occupancy in the Greater ABC Area, during the period 1995 to 2005. The first chapter points the influence of macroeconomic policy, since Economic Collor Plan, over the labour market of the industry. The second chapter describes the Industrial Occupancy in Brazil, focusing the profile of the workers allocated on the Brazilian industry sector. The third chapter analysis the profile changing on the industries of Great ABC Area, showing up local characters, changes in organizational framework, technological change and productivity. The fourth chapter introduces a discussion about the workers allocation on the industries of Great ABC Area, with special attention on the behavior of indicators related to the level of occupancy and the profile of industries located on Great ABC Area